Nuclear energy security : a critical analysis of the North-South diplomatic discourse on the nuclear fuel cycle, 2004-2011 - Spies, Yolanda Kemp (University of Pretoria, 2013)
Mini Dissertation (MA (Diplomatic Studies))--University of Pretoria, 2012.